2021
DOI: 10.1007/s11340-021-00690-0
|View full text |Cite
|
Sign up to set email alerts
|

Displacement Uncertainty Quantifications in T3-Stereocorrelation

Abstract: Background: Uncertainty quantifications are required for any measurement result to be meaningful. Objective: The present work aims at deriving and comparing a priori estimates of displacement uncertainties in T3-stereocorrelation for a setup to perform high temperature tests. Methods: Images acquired prior to the actual experiment (i.e., at room temperature) were registered using 3-noded triangular elements (T3-stereocorrelation) to determine displacement uncertainties for different positions of the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…For artificial cases, the multiplicative constant Σ u was found equal to 1.2 ± 0.3 for global T3-stereocorrelation [25]. More refined analyses have shown that a lower bound to Σ u was 1.08 [21] when threenoded elements were used. This last value was selected for the results reported herein.…”
Section: Displacement Uncertaintiesmentioning
confidence: 93%
See 2 more Smart Citations
“…For artificial cases, the multiplicative constant Σ u was found equal to 1.2 ± 0.3 for global T3-stereocorrelation [25]. More refined analyses have shown that a lower bound to Σ u was 1.08 [21] when threenoded elements were used. This last value was selected for the results reported herein.…”
Section: Displacement Uncertaintiesmentioning
confidence: 93%
“…Such approaches allow the systemic errors to be avoided. However, they may occur in practice, and the previous analyses call for experimental validations [20,21]. As maturity increases in the use of stereocorrelation, some systemic errors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nodal displacement can be obtained through a Gauss-Newton scheme [16,32]. Hence, at each iteration, the stereocorrelation Hessian matrix [H U ] and second member {h U } are computed…”
Section: Finite Element Formulation Of Stereocorrelation (Fe-sc)mentioning
confidence: 99%
“…Multiscale and multiview DIC approaches were developed separately in previous works. Measurement uncertainties in DIC depend on the number of pixel per the size of subsets in the local approaches [32,31,17] or element size in global approaches [15,6]. For a given resolution, bigger elements contain more pixels and thus yield lower measurement uncertainties.…”
Section: Introductionmentioning
confidence: 99%